2019
DOI: 10.1128/mra.00303-19
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Enterococcus durans OSY-EGY, a Multiple-Antimicrobial-Peptide Producer Isolated from Egyptian Hard Cheese

Abstract: Enterococcus durans OSY-EGY was isolated recently from cheese. The strain produces potent antimicrobial agents. Here, we present the draft genome sequence of the strain, with a genome size of 3,230,625 bp and an average G+C content of 37.69%. Draft genome mining identified several biosynthetic gene clusters encoding multiple antimicrobial peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…A new lactic acid bacterium strain, E. durans OSY-EGY, was isolated from an artisanal cheese and found to have a promising antimicrobial activity that could be beneficial in food applications (Hussein et al, 2019). Before proposing the use of the strain in further industrial applications, research is needed to assess its safety, antimicrobial, and probiotic traits.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A new lactic acid bacterium strain, E. durans OSY-EGY, was isolated from an artisanal cheese and found to have a promising antimicrobial activity that could be beneficial in food applications (Hussein et al, 2019). Before proposing the use of the strain in further industrial applications, research is needed to assess its safety, antimicrobial, and probiotic traits.…”
Section: Resultsmentioning
confidence: 99%
“…Screening E. durans OSY-EGY Genome for Safetyand Probiotic-Related Traits For safety assessment, E. durans OSY-EGY genome (Hussein et al, 2019) was screened using the Comprehensive Antibiotic Resistance Database (CARD) (Jia et al, 2017) and Virulence Factor of Bacterial Pathogens Database (VFDB) 1 (Chen et al, 2005). Additionally, E. durans OSY-EGY genome was mined for genes associated with biosynthetic pathways of biogenic amines using KAAS-KEGG Automatic Annotation Server 2 (Moriya et al, 2007) and KEGG Mapper 3 (Kanehisa et al, 2019).…”
Section: Genotypic Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ED26E/7 was hemolysis and gelatinase-negative. The bacteriocin-producing species strain E. durans was also isolated from important Egyptian cheese OSY-W [ 55 ]. Pieniz et al [ 56 ] described E. durans LAB18s isolated from Brazilian soft cheese with the antioxidant activity of its culture supernatant and intracellular extract.…”
Section: Discussionmentioning
confidence: 99%
“…Pieniz et al [ 56 ] described E. durans LAB18s isolated from Brazilian soft cheese with the antioxidant activity of its culture supernatant and intracellular extract. Further beneficial/desirable traits may include the production of antioxidants or the expression of pathogens antagonism [ 55 ]. Dvorožňáková et al [ 57 ] reported the highest stimulative effect on phagocytosis induced by E. durans ED26E/7 strain in mice infected with Trichinella spiralis .…”
Section: Discussionmentioning
confidence: 99%